Magnetic Field Annihilation in a Magnetotail Electron Diffusion Region With Electron‐Scale Magnetic Island. Issue 7 (7th July 2022) - Hasegawa, H.; Denton, R. E.; Nakamura, T. K. M.; Genestreti, K. J.; Phan, T. D.; Nakamura, R.; Hwang, K.‐J.; Ahmadi, N.; Shi, Q. Q.; Hesse, M.; Burch, J. L.; Webster, J. M.; et al.
Abstract: We present observations in Earth's magnetotail by the Magnetospheric Multiscale spacecraft that are consistent with magnetic field annihilation, rather than magnetic topology change, causing fast magnetic‐to‐electron energy conversion in an electron‐scale current sheet. Multi‐spacecraft analysis for the magnetic field reconstruction shows that an electron‐scale magnetic island was embedded in the observed electron diffusion region (EDR), suggesting an elongated shape of the EDR. Evidence for the annihilation was revealed in the form of the island growing at a rate much lower than expected for the standard X‐type geometry of the EDR, which indicates that magnetic flux injected into the EDR was not ejected from the X‐point or accumulated in the island, but was dissipated in the EDR. This energy conversion process is in contrast to that in the standard EDR of a reconnecting current sheet where the energy of antiparallel magnetic fields is mostly converted to electron bulk‐flow energy. Fully kinetic simulation also demonstrates that an elongated EDR is subject to the formation of electron‐scale magnetic islands in which fast but transient annihilation can occur. Consistent with the observations and simulation, theoretical analysis shows that fast magnetic diffusion can occur in an elongated EDR in the presence of nongyrotropic electron effects. We suggest that the annihilation in elongated EDRs may contribute to the dissipation of magnetic energy in a turbulent collisionless plasma. Plain Language Summary: Magnetic reconnection in electric current sheets is the key to fast release of magnetic energy in many space and astrophysical plasma systems, such as during magnetospheric substorms and solar flares. Establishing the mechanism by which magnetic energy is converted to particle energy in the reconnection process is the key to understanding the large‐scale impacts of reconnection, including energy partition and particle acceleration. It is generally believed that an electron‐scale diffusion region (EDR), where a magnetic‐to‐electron energy conversion occurs, has an X‐type magnetic field geometry around which the energy of antiparallel magnetic fields injected into the EDR is mostly converted to the bulk‐flow energy of electrons by magnetic tension of reconnected field lines. Contrary to this standard X‐type magnetic field geometry of reconnection, we report observations in Earth's magnetotail by NASA's Magnetospheric Multiscale spacecraft showing that the EDR can be highly elongated. The important and surprising consequence of the observed elongated shape of the EDR is that the fast energy conversion in the EDR can be caused mostly by magnetic field annihilation, rather than magnetic topology change. The fast collisionless annihilation that we discovered is fundamentally different from the classical magnetic field annihilation due to collisional and wave‐induced resistivity. Key Points: Multi‐spacecraft observations consistent with magnetic field annihilation in an electron diffusion region (EDR) of magnetotail reconnection Magnetic field reconstruction suggests that an electron‐scale magnetic island was embedded in the EDR with elongated shape Theoretical analysis shows that fast collisionless magnetic diffusion can occur in the elongated part of EDR with nongyrotropic electrons